FAKTOR EKSTERNAL DAN INTERNAL PEMASARAN COKELAT BATANGAN ASAL RUMAH PRODUKSI COKELAT MANSEL KABUPATEN MANOKWARI SELATAN - Deasi Mayawati; Waromi, Josina; Trees Augustine Pattiasina; Mutmardiyah Irianti (Sosio Agri Papua, 2024)
The right marketing strategy is the main key to sustainable marketing activities. The purpose of this research is to (1) identify the internal and external factors affecting the Mansel Chocolate Production House business and (2) develop a suitable marketing strategy for its implementation. A descriptive method employs a survey approach. Data analysis uses SWOT analysis. The research results show: The Internal Strategy Analysis Factor Matrix, which is based on strength factors, scored 2.44, while the score for weaknesses is 1.17. The Strategy Analysis External Factor Matrix shows that the opportunity factor has a score of 0.67, and the threat has a score of 0.96. The Mansel Chocolate Production House can implement the following marketing strategies: the SO (Strength-Opportunity) Strategy, "Creating quality products and distinctive tastes," the WO (Weakness-Opportunity) Strategy, "Increasing machine capacity with partners (Bank Indonesia)," the ST (Strength-Threat) Strategy, "Maintaining product quality and making various chocolate variants," and the WT (Weakness-Threat) Strategy, "Making packaging more interesting and new variants in terms of shape and taste."